Answer :

Given:-


Take



We know that, Formula








5x = 6 – x2


x2 + 5x – 6 = 0


x2 + 6x – x – 6 = 0


x(x + 6) – 1(x + 6) = 0


x = –6, 1


as given


0<x< √6


Therefore


x = 1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers